Advokasi Perilaku Ibu Generasi Milenial Menggunakan Alat Kontrasepsi IUD Di Puskesmas Pacar Keling Kota Surabaya - Ravitasari, Dayne Sherlia; Devy, Shrimarti Rukmini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Background: Indonesia's population is 270.20 million people. Family planning is a government effort that aims to control the rate of population growth. Millennial mothers prefer to use injectable contraceptive methods. Meanwhile, the Indonesian government prioritizes the IUD family planning program. Research Objectives: The research objective is to analyze factors related to the behavior of millennial mothers in choosing to use family planning injections in the city of Surabaya. Research Method: The research method uses a literature review with sources via Google Scholar. Research Results: Advocacy was carried out with the headman and sub-district heads as decision-makers. The target is millennial mothers aged 22–42 years in the Pacar Keling Health Center area of Surabaya City. Conclusion: Advocacy is aimed at involving commitment and support from stakeholders so that the government's goals for the IUD program are achieved.Keywords: Family planning; Millenial mothers; Advocacy